Opavivará!: modos de vida na arte contemporânea - Campos, Livia Fernandes (2024)
OPAVIVARA! is an art collective from Rio de Janeiro that since 2005 has carried out actions in public spaces and cultural institutions. The collective presents its actions as interactive proposals that privilege the participation of groups of different people in projects in which the occupation of local spaces and the exploration of experimental forms of socialization are associated, and that become possible from relational devices elaborated by the group. These projects articulate ideas and practices, ways of life and objects, imaginaries and new forms of exchanges that always carry the signature OPAVIVARÁ!, and not the individual names of the artists that make up the collective. Based on your proposals, OPAVIVARÁ! often highlights social and political conflicts, without apparently presenting a lasting artistic project. Their actions subjectively provoke other ways of experiencing local spaces and realities and intend to propose alternative ways of interaction between individuals and between them and the urban space. In this dissertation, we will investigate how the collective's proposals are structured and how they contribute to discussions about contemporary art.